Processed fruit juice ready to drink: screening acute toxicity at the cellular level (Acta Scientiarum. Biological Sciences, 2017)
The present study evaluated the acute toxicity at the cellular level of processed juice ready for consumption Orange and Grape flavors, produced by five companies with significant influence on the food market of South American countries, especially in Brazil. This evaluation was performed in root meristem cells of Allium cepa L., at the exposure times of 24 and 48 hours, directly with marketed liquid preparations. Based on the results, it was found that fruit juices, of all companies considered, promoted significant antiproliferative effect to root meristems at the exposure time of 24 hours and resulted in at both exposure times, statistically significant number of mitotic spindle changes and chromosomal breaks. Therefore, under the study conditions, all juice samples analyzed were cytotoxic, genotoxic and mutagenic to root meristem cells. These results indicate that such beverages have relevant potential to cause cellular disorders and, thus, need to be evaluated more fully in more complex test systems, as those in rodents, and then establish specific toxicity at the cellular level of these juices and ensure the well-being of those who consume them.